My Arm - Balatiah, Razan; Mahmoud, Sara (My University, 2018)
My Arm is a project depends on a hand gestures by using a glove instead of using remote controls to achieve more than one target by using Arduino and some of hardware tools . First of all a robot that will help the user to control the direction of the car was designed, so that this car can cross the right path in different mazes,also it can remembers directions, and it can avoids barriers during movement by issuing a sound from Buzzer to alert the user . The robot designed using Arduino and consists mainly of transmitter and receiver, the transmitter part can transmit different signals by different gestures from the arm of the user, and the car represent the receiver part which directed in different direction as forward, backward, left, right, stop moving and it can save the path to repeat it. Also it controls the speed by using flex sensor through the movement of the finger. Secondly a small educational tool for children was designed to facilitate learning of directions through a group of leds that light up on hand gestures. These movements can also be memorized and returned again to facilitate learning. The importance of the project is to save time and effort on the user who can control this car remotely without having to move it with his/her hands such that the control of the car through hand gesture is easier and more practical than remote or regular buttons. Also it is a game that the user feels happy and has fun while controlling the car to cross the right path in the maze. And to facilitate learning of directions for the children . The first step is to get all data and tools needed while developing the project by reading articles and research, then start analysing this data and get the results that help to know how to use the data and tools in a suitable way. After a deep search, we came up with a result that robots are very modern field in technology that everyone seeks to develop rather than old techniques such as buttons and also there are many projects and research done in this field.